2023
DOI: 10.1002/jnr.25204
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial direct current stimulation alleviates nociceptive behavior in male rats with neuropathic pain by regulating oxidative stress and reducing neuroinflammation

Abstract: Transcranial direct curent stimulation (tDCS) and trans‐spinal direct current stimulation (tsDCS) are promising therapies for pain that can alter the excitability of neuronal activity in cerebral cortex. The aim of the study is to investigate the therapeutic effects of direct current stimulation (DCS) over the spinal cord and cerebral cortex on oxidative stress and neuroinflammation in rats with chronic constriction injury (CCI). Male Wistar rats were randomly divided into four experimental groups: Sham, CCI, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 98 publications
(127 reference statements)
0
0
0
Order By: Relevance
“…In contrast, we observed that 200 mg/kg ginger treatment improved both locomotor activity and thermal allodynia. NP begins to occur on the 7th day after surgery in animals with nerve damage [ 2 ]. Borgonetti et al started treatment on day 3 after surgery, whereas we started the ginger treatment on the 7th day after surgery and applied it for 7 days; this might explain the different results for improvement in locomotor activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, we observed that 200 mg/kg ginger treatment improved both locomotor activity and thermal allodynia. NP begins to occur on the 7th day after surgery in animals with nerve damage [ 2 ]. Borgonetti et al started treatment on day 3 after surgery, whereas we started the ginger treatment on the 7th day after surgery and applied it for 7 days; this might explain the different results for improvement in locomotor activity.…”
Section: Discussionmentioning
confidence: 99%
“…Proinflammatory cytokines are important in the development and maintenance of NP [ 44 ]. NP is characterised by glial cell activation and proinflammatory cytokine secretion in the spinal dorsal horn [ 2 ]. TNF-α is one of the most potent proinflammatory cytokines expressed by microglia, astrocytes, and primary sensory dorsal root ganglion neurons [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation